Hungarian destinations affected by slow tourism - present and future - Szőke, Tünde Mónika (Észak-magyarországi Stratégiai Füzetek, 2023)
This study examines the scientific publications on slow tourism published in Hungary, focusing on literature covering destinations that have proposed slow tourism as a development direction. The present study includes two thematic maps. The first contains the municipalities and regions where a grassroots initiative related to slow tourism exists. The second map has been extended to include the planned development sites. Based on this, the study recommends how the national tourism managment can integrate slow tourism into the domestic tourism mainstream.